Competing in COVID era by adopting defensive marketing strategies - Kumar, Amit; Kaur, Anupriya (Gyan Management Journal, 2021)
The epidemic of novel corona virus (COVID-19) has created global health crises. Corona virus has a wide-reaching effect on almost every business.. This pandemic continues to impose the temporary closure of businesses and to follow lockdown measures. In a short span, COVID-19 has changed the lives and livelihoods of people around the globe and enforced businesses to understand the impact of COVID-19 on businesses and to react properly in this uncertain situation. Businesses must realize that in this environment of fear, confusion, and concern they need engage with their clients and use CRM tactics to get closer to their customers. Businesses are facing various challenges regarding consumer demand and marketing, sales growth, and revenue earning. This drastic event has slow down the pace of businesses and their strategies to attract new customers for business, therefore, raised the importance of defensive marketing strategies (Holding existing customers or customer retention). The current article provides businesses some insights to understand and implement defensive marketing strategies in and after the time of COVID-19.